Risk assessment and antibody responses to SARS-CoV-2 in healthcare workers - Bansal, Amit; Trieu, Mai-Chi; Mohn, Kristin G. I.; Madsen, Anders; Olofsson, Jan Stefan; Sandnes, Helene Heitmann; Sævik, Marianne; Søyland, Hanne; Hansen, Lena; Onyango, Therese Bredholt; Tøndel, Camilla; Brokstad, Karl Albert; et al. (Frontiers in Public Health, 2023)
Among Norwegian healthcare workers, we found moderate SARS-CoV-2 infection rates (10.5%) in 2020. Infection was associated with household and occupational exposure to SARS-CoV-2. HCWs infected with SARS-CoV-2 had durable antibodies (half-life 4.3 months) and higher titres post-vaccination than non-infected HCWs. Author contributions: RJC, NL, KAB, KGIM, and CT conceptualized and organised the study. HHS, MS, HS, ÅG, KGIM, AB, JSO, MCT and TBO collected case report forms and/or sera. AM, JSO, TBO, LH, MCT and AB performed experiments. AB visualized the data, performed statistical and meta-analyses, and wrote the original draft. All authors reviewed and amended the draft.